Pengaruh Hutang Jangka Panjang Dan Hutang Jangka Pendek Terhadap Profitabilitas Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Indeks Saham Syariah Indonesia (Issi) - Nurjanah (FEBI IAIN Langsa, 2023)
This study aims to determine the effect of long-term debt and short –term bedt on profitability in food and beverage sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI). Quantitative research methods using secondary data. The analysis technique uses panel data regression analysis. The population in this study included all companies in the food and beverage sub-sector eith a purposive sampling technique and 13 companies were obtained as research samples. The research period is 2016-2021. The results show that partially, long termdebt has a significant negative effect on profitability with a tvalue 2.256 > ttables 1.665 with a significance level of 0,02 < 0,05. Short term debt has no effect on probability with a tvalue 1.324 < ttables 1.665 with a signifikan level of 0.08. meanwhile, simultaneously long term debt and short term debt have an effect on probability with a Fvalue 2.587 > Ftables 2.370.